Template-free synthesis of hybrid silica nanoparticle with functionalized mesostructure for efficient methylene blue removal. (March 2021) - Parida, Dambarudhar; Salmeia, Khalifah A.; Sadeghpour, Amin; Zhao, Shanyu; Maurya, Anjani K.; Assaf, Khaleel I.; Moreau, Eva; Pauer, Robin; Lehner, Sandro; Jovic, Milijana; Cordula, Hirsch; Gaan, Sabyasachi
Abstract: A simple one-pot synthesis process for functionalized mesostructured silica nanoparticles (MSNP) is reported. The novel process demonstrated the possibility to achieve MSNP with a surface area up to 501 m 2 .g −1 using a phosphonate based nonsilane precursor such as N, N´-bis[4, 6-bis(diethylphosphono)-1, 3, 5-triazin-yl]-1, 2-diaminoethane (ED). MSNP obtained by using 20 mol% of ED achieved a surface area of 80 m 2 .g −1 and increasing the ED content to 30 mol% resulted in a surface area of 501 m 2 .g −1 . Zeta potential of novel MSNPs (−65.5 and 70.0 mV) were much higher than the nanoparticle (NP) prepared from only TEOS (−49 mV), indicating the presence of a large number of –SiOH and phosphonic acid surface functional groups, as confirmed by Fourier-transform infrared spectroscopy (FT-IR) and Nuclear magnetic resonance (NMR) analysis. The functionalized MSNPs were used as an adsorbent for the removal of cationic pollutants like methylene blue (MB). The MSNP with the highest porosity displayed favorable MB adsorption behavior with ~380 mg.g −1 of MB adsorption capacity. Facile regeneration in an acidic medium (~pH 4.5) with easy recyclability (10 cycles) confirmed the practical applicability of this novel functionalized MSNPs. Graphical abstract: Unlabelled Image Highlights: Template free route for hybrid silica nanoparticles with ~500 m 2 .g −1 surface area. Cocondensation of a nonsilane precursor to achieve phosphonic acid functionality. Silica nanoparticles displayed high Methylene blue adsorption (380 mg.g −1 ). This method broaden the precursor selection for mesoporous silica synthesis.